Ekonomi Islam di Mata Intelektual Non-Muslim: Telaah atas Pemikiran John L. Esposito - Ubaidillah, Ahmad; Ulum, Khozainul (Universitas Islam Lamongan, 2025)
This article aims to examine the Islamic economic thought of a non-Muslim intellectual, John L. Esposito. What are the themes of Islamic economics discussed by Esposito? Those are the questions that will be answered in this study. This research is a library research. In collecting data, the author utilizes secondary sources in the form of journals, books, dictionaries, magazines, and other sources. The analytical method used is hermeneutics, which is tasked with interpreting, explaining, interpreting, and translating Esposito's views on Islamic economics. The results of the study conclude that Esposito, as a non-Muslim intellectual, understands Islamic economics as part of the broader teachings of Islam, focusing on ethics, social justice, and distribution of wealth. This economic system, according to Esposito, is based on the principles of the Qur'an and Sunnah which aim to create social welfare through economic justice, prohibition of exploitation, and equality. He describes Islamic economics as a tool to achieve social harmony and shared prosperity. Thus, Islamic economics is seen as a means to achieve justice and shared prosperity in society.